1566. Is Primary CMV Infection Post-transplant Influenced by Circadian Rhythms?. (26th November 2018) - Rafferty, Hannah; Tam, Jerry; Smith, Colette; Reeves, Matthew; McKeating, Jane; Sharma, Dinesh; Whitmore, David; Griffiths, Paul
Abstract: Background: Cytomegalovirus (CMV) infection causes significant morbidity after transplant. Patients can be stratified by donor and recipient CMV serostatus, but the infection phenotype remains variable. We hypothesized that some of this variability might be explained by circadian rhythms influenced by time of transplant. Methods: Virological, demographic and transplant data were reviewed for liver and kidney transplant patients ( n = 1, 111) managed between 2002 and 2015 using pre-emptive therapy. Donor circulatory arrest time and reperfusion time in the recipient were split into four categories, chosen a priori . Patients were categorised into three groups depending on donor and recipient CMV serostatus. Differences between groups were assessed using chi-squared and Kruskall–Wallis tests. Results: For the donor seropositive/recipient seronegative group (D+R−) all CMV parameters were highest when reperfusion occurred in the day or evening, and the lowest in the night or morning (see table). Conclusion: Time of day of transplant surgery appears to be associated with development of CMV viraemia and the parameters of infection in one subgroup of transplant patients. These differences could be explained by circadian rhythms of CMV replication and/or immunological parameters varying throughout the day. These data therefore provide support for further study of circadian effects on CMV replication and host CMV immunity. Disclosures: P. Griffiths, shire: Scientific Advisor, funds paid to my institution not to me; chimerix: Scientific Advisor, funds paid to my institution not to me; sanofi pasteur: Grant Investigator, funds paid to my institution not to me; genentech: Scientific Advisor, funds paid to my institution not to me.